2021
DOI: 10.1186/s12888-021-03535-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mental health symptoms during the COVID-19 pandemic in ophthalmic personnel and students in USA (& Canada): a cross-sectional survey study

Abstract: Background The COVID-19 pandemic poses mental health challenges to frontline healthcare workers. Eye care professionals may be especially susceptible to mental health problems due to high-risk exposures to patients. Yet, no prior research has studied mental health issues among eye care professionals during the COVID-19 pandemic. Objective The purpose of this study was to identify risk factors for mental health problems during the COVID-19 pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Working in pandemic conditions has been a special challenge for physicians, nurses, and other medical professionals, even though in many regions the pandemic has largely subsided and restrictions have been lifted. By doing their everyday tasks, medical professionals run the risk of losing their lives or health, which results in intense daily stress ( Pang et al, 2021 ; Giorgi et al, 2020 ; Ali et al, 2020 ). The psychological impact of COVID-19 also includes burnout affecting health care workers ( Doolittle, Anderssen & Perreaux, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Working in pandemic conditions has been a special challenge for physicians, nurses, and other medical professionals, even though in many regions the pandemic has largely subsided and restrictions have been lifted. By doing their everyday tasks, medical professionals run the risk of losing their lives or health, which results in intense daily stress ( Pang et al, 2021 ; Giorgi et al, 2020 ; Ali et al, 2020 ). The psychological impact of COVID-19 also includes burnout affecting health care workers ( Doolittle, Anderssen & Perreaux, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Four studies reported on mental health impacts of the COVID-19 pandemic on Black people in Canada. 38 , 47 , 50 , 51 A qualitative study found that online misinformation about COVID-19 aggravated mental health issues among Black Canadians and resulted in fear of and anger about mandatory vaccine orders. 38 Some Black community members were afraid of being stigmatized whether they received or declined the COVID-19 vaccine, which amplified their anxiety about COVID-19 and prevented them from getting vaccinated or promoting vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…The ongoing PCC presence adds fear and burden to healthcare professionals who are already experiencing chronic stress and its adverse impact on their health. 9 , 12 …”
Section: Introductionmentioning
confidence: 99%